Household energy efficiency and health: Area-level analysis of hospital admissions in England - Sharpe, RA; Machray, KE; Fleming, LE; Taylor, T; Henley, W; Chenore, T; Hutchcroft, I; Taylor, J; Heaviside, C; Wheeler, BW (Elsevier, 2019)
Introduction: Fuel poverty affects up to 35% of European homes, which represents a significant burden on society and healthcare systems. Draught proofing homes to prevent heat loss, improved glazing, insulation and heating (energy efficiency measures) can make more homes more affordable to heat. This has prompted significant investment in energy efficiency upgrades for around 40% of UK households to reduce the impact of fuel poverty. Despite some inconsistent evidence, household energy efficiency interventions can improve cardiovascular and respiratory health outcomes. However, the health benefits of these interventions have not been fully explored; this is the focus of this study.